2015
DOI: 10.1080/07347324.2015.1050929
|View full text |Cite
|
Sign up to set email alerts
|

Congress 60: An Addiction Recovery Community within the Islamic Republic of Iran

Abstract: The Islamic Republic of Iran, in response to the highest rate of opium consumption in the world, has devoted substantial resources to reduce drug availability and address addiction-related problems. Demand-reduction activities have included residential rehabilitation centers, outpatient treatment centers, and support for addiction recovery mutual aid organizations such as Narcotics Anonymous. The growing role of voluntary nongovernmental organizations (NGOs) in supporting addiction recovery in Iran has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Founded in 1998 in Iran, Congress 60 is a nongovernmental organisation that as of 2015 had over 20 000 members. Differing from other international mutual-help groups, such as Narcotics Anonymous, Congress 60 promotes a simultaneously biological, psychological, social and spiritual understanding of addiction and recovery [17]. The OT-assisted treatment protocol for OUD was approved in 2011 by the Iranian Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%
“…Founded in 1998 in Iran, Congress 60 is a nongovernmental organisation that as of 2015 had over 20 000 members. Differing from other international mutual-help groups, such as Narcotics Anonymous, Congress 60 promotes a simultaneously biological, psychological, social and spiritual understanding of addiction and recovery [17]. The OT-assisted treatment protocol for OUD was approved in 2011 by the Iranian Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%
“…117 , 118 Unemployment and financial distress are two main causes of mental conditions in Iran. 119 A study in the province of Ghazvin showed that unemployment, inflation and welfare inequality had a meaningful relation with suicide rates. 120 Another example is the impacts of economic decline on drug addicts and their families.…”
Section: Part 1) Iranian’s Enjoyment Of Their Rights In Sanctions’ Pementioning
confidence: 99%
“…Congress 60 program consists of the DST method (an 11-month process of drug tapering using opium tincture) combined with intensive psychosocial support provided within a philosophy of recovery. Congress 60 offers educational classes and group therapy to promote positive thinking and mental balance ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%